Hypertension unawareness among Chinese patients with first-ever stroke - Qinqin Cao; Pei Pei; Jun Zhang; Jillian Naylor; Xinying Fan; Biyang Cai; Qiliang Dai; Wen Sun; Ruidong Ye; Ruifeng Shi; Keting Liu; Yongjun Jiang; et al. (BMC, 2016)
Abstract Background The low rates of hypertension treatment and control, partly due to its unawareness, are the main causes of the high stroke incidence in China. The purpose of this study was to evaluate hypertension unawareness amongst patients with first-ever stroke and to detect factors associated with its unawareness. Methods We selected those diagnosed with hypertension from patients with first-ever stroke registered in the Nanjing Stroke Registry Program between 2004 and 2014. These hypertensives were divided as being aware or unaware of their hypertension by using a brief questionnaire conducted shortly after the stroke. Multivariate logistic regression analysis was performed to identify potential factors associated with hypertension unawareness. Results Of the 5309 patients with first-ever stroke, 3732 (70.3 %) were diagnosed with hypertension. Among which, 593 (15.9 %) were unaware of their hypertension at the time of stroke onset. Lower-level of education (primary school or illiteracy) and smoking were associated positively with hypertension unawareness; while advanced age, overweight, diabetes mellitus, heart diseases and family history of stroke were associated negatively with hypertension unawareness. Annual data analyzed indicated that the rate of hypertension awareness increased during the past 11 years (r = 0.613, P = 0.045 for trends). Conclusions A substantial proportion (15.9 %) of Chinese patients with hypertension had not been aware of this covert risk until an overt stroke occurred. Hypertension unawareness was associated with lower educational levels and smoking, which address the importance of health education especially in these individuals.